Textual Interaction in Alaa Mashdoub’s Novels - Hasan, Nagham Falah; Mohammed, Bushra Yaseen (Al-Adab Journal, 2021)
Textual interaction: is textual exchange, which is a translation of the French term (intertext), as intertwining is a feature that distinguishes texts, especially literary ones, so there is hardly a text devoid of correlation with other texts prior to it, and Bakhtin is considered the first to turn to the concept of dialogue in discourse in general. And the narrative discourse in particular, and Julia Christeva, who is credited with developing the term intertextuality, saw that intertextuality is essential in all texts that are made through absorption, and at the same time through the demolition of other texts of the intertwined space. As for Gérard Genet, he called intertextual transcendence "textual transcendence", while Roland Barthes argued that intertextuality is in reality the impossibility of living outside the infinite text, whether that text is Prost, the daily newspaper, or the television screen, so he sees that intertextuality is necessary in books and magazines. And newspapers or stories and novels, and even in other fields such as radio and television, it is not possible to escape from intertextuality, as there is no very innocent text devoid of textual relationships with other texts, while Saeed Yaktuin called the term “textual interaction” as a synonym for intertextuality, and he justified his choice of this term specifically That he is deeper in carrying the intended meaning and suggesting it in a proper and proper manner, and Saeed Qakot, using the term "textual interaction", has taken the intertextuality out of the angle of accusation or theft.